The importance of trust for partnership and collaboration in volatile economic conditions - Gür, Nurullah; Alayoğlu, Nihat (Springer International Publishing Ag, 2017)
Volatile economic conditions are painful for most firms. Firms struggle to survive when market demand is sluggish, uncertainties are high, and credit conditions are tight. Therefore, maintaining and strengthening partnerships, retaining existing customers or finding new ones through innovation, and finding external finance are extremely vital to keep firms alive during volatile economic conditions. In this chapter we argue that trust plays a key role in protecting strong relationships with partners, customers, suppliers, and other actors or when developing new relationships. Trust might help to protect partnerships and establish collaborative relationships by mitigating asymmetric information and free-rider problems, allowing for more open and honest information sharing and restraining opportunistic behaviour.
WOS: 000415645900012